Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/ecog.02817
|View full text |Cite
|
Sign up to set email alerts
|

A recipe for scavenging in vertebrates – the natural history of a behaviour

Abstract: Despite its prevalence, the importance of scavenging to carnivores is difficult to ascertain in modern day forms and impossible to study directly in extinct species. Yet, there are certain intrinsic and environmental features of a species that push it towards a scavenging lifestyle. These can be thought of as some of the principal parameters in optimal foraging theory namely, encounter rate and handling time. We use these components to highlight the morphologies and environments that would have been conducive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 121 publications
0
37
0
1
Order By: Relevance
“…It may be true that facultative scavengers reduce their search efficiency for carrion when carrion densities are low, and alternatively increasingly target live prey if more available, which is consistent with optimal foraging theory (Kane et al . ; Margalida et al . ).…”
Section: Apex Facultative Scavenger Modelmentioning
confidence: 99%
“…It may be true that facultative scavengers reduce their search efficiency for carrion when carrion densities are low, and alternatively increasingly target live prey if more available, which is consistent with optimal foraging theory (Kane et al . ; Margalida et al . ).…”
Section: Apex Facultative Scavenger Modelmentioning
confidence: 99%
“…The resulting population sizes were then halved because (i) vultures tend not to forage everyday especially during the breeding season where they exhibit biparental care (Mundy ) and (ii) the other species tend to be facultative rather than obligate scavengers (Kane et al . ). Given that the eagle numbers are extrapolated from transect counts, which may be biased by transient individuals, we ran each model again with half the predicted population for eagles (40 instead of 80).…”
Section: Methodsmentioning
confidence: 97%
“…Dominance was sized-based and the hierarchy from most dominant to least dominant was hyena, jackal, LFV, AWBV, eagle (Attwell 1963;Kendall 2013;Kruuk 1967;Mundy 1992 (Mundy 1992) and (ii) the other species tend to be facultative rather than obligate scavengers (Kane et al 2016). Given that the eagle numbers are extrapolated from transect counts, which may be biased by transient individuals, we ran each model again with half the predicted population for eagles (40 instead of 80).…”
Section: Dominance Rankmentioning
confidence: 99%
“…Indeed, most large mammalian carnivores shift facultatively between hunting and scavenging depending on the regional, seasonal, and spatial variation in the susceptibility of their prey to mortality . Scavenging opportunities are dependent on the density, size, and quality of carcasses encountered, and species that rely on scavenging to sustain a significant portion of their diets must encounter enough carrion to meet their dietary needs . The encounter rate is in turn dependent on the ecology of the local carnivore and herbivore populations including carnivore species density and degree of sociality, carnivore feeding preferences and specializations, predator to prey ratios, and prey biomass and densities .…”
Section: How Much Meat and Marrow Would Scavenging Early Hominins Havmentioning
confidence: 99%
“…In fact, Bickerton and Szathmáry suggested that language and cooperation on a human scale are so distinct from behaviors in other primates that they required a trigger of some kind—and they suggest the only activity practiced by hominins that contained all the necessary components for that trigger was confrontational scavenging . The emergence of endurance running has even been proposed as an adaptation to securing sufficient access to scattered and ephemeral carcasses, or to signal the location of carrion to others, although this behavior is more often linked to hunting live prey …”
Section: What May Have Been Some Potential Behavioral Consequences Ofmentioning
confidence: 99%